2008
DOI: 10.1007/s10194-008-0055-5
|View full text |Cite
|
Sign up to set email alerts
|

Locus of control moderates the relationship between headache pain and depression

Abstract: The aim of the current study was to triangulate qualitative and quantitative data in order to examine in greater detail the relationship between self-reported headache pain severity, depression and coping styles. Psychosocial scales, headache characteristic scales and in-depth interviews were administered to 71 adults with the diagnosis of primary headache. Regression analyses with the scales showed that greater self-reported headache pain severity was associated with higher levels of depression. A high intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 39 publications
4
22
0
Order By: Relevance
“…Negative emotional states, including anxiety, depression and anger, are associated with headache triggers, intensity of headache pain, and response to treatment [46, 47]. Coping skills have also been shown to moderate the relationship between headache severity and depression [48]. …”
Section: Discussionmentioning
confidence: 99%
“…Negative emotional states, including anxiety, depression and anger, are associated with headache triggers, intensity of headache pain, and response to treatment [46, 47]. Coping skills have also been shown to moderate the relationship between headache severity and depression [48]. …”
Section: Discussionmentioning
confidence: 99%
“…Those who perceive that stress affects their health may have an external locus of control, believing that their health is not in their control, but attributable to external circumstances. Studies have indicated that individuals who have a high external locus of control experience worse outcomes than those who feel that their health is within their control (Heath, Saliba, Mahmassani, Major, & Khoury, 2008; Preau et al, 2005). Although much of this research has focused on those with an illness, the present study suggests that health-related locus of control (as seen in a greater perceived impact of stress on health) may also contribute to outcomes in healthy populations.…”
Section: Discussionmentioning
confidence: 99%
“…Specifi c cognitive goals include enhancing self-effi cacy (ie, the patient's belief in his or her ability to succeed or accomplish a certain task), and helping patients gain an internal locus of control (ie, a belief that the mechanism for change lies within oneself) as opposed to an external locus of control (ie, the belief that only the physician, medication, or medical procedures have the power for change) [32]. Research has demonstrated that both poor self-effi cacy and external locus of control predict poorer outcomes [33,34]. CBT also may focus on changing "catastrophizing," a hopeless and overwhelming thinking pattern that has been shown to predict poor outcome and reduced quality of life.…”
Section: Patient Education For Migraine and Medication Overuse Headachementioning
confidence: 98%